Non-pharmacological interventions for postpartum depression: A protocol for systematic review and network meta-analysis. Issue 31 (31st July 2020) - Wang, Yang; Li, Hui; Peng, Wei; Chen, Yalin; Qiu, Mimi; Wang, Jun; Hao, Qinghong; Tu, Yang; Liu, Yunlu; Zhu, Tianmin
Abstract: Background: Postpartum depression (PPD) is one of the most common mental disorders in women following childbirth with heightened prevalence across the globe. Both pharmacotherapy and non-pharmacological interventions are effective for PPD. However, due to the concerns about the side effect on the mother and child of pharmacological treatments, most of women with PPD choose non-pharmacological therapies as their first line option. Prescription of these non-drug approaches should be guided by high quality evidence. Therefore, this network meta-analysis aims to compare, rank and interpret existed non-pharmacological evidence for the effective treatment of women with PPD. Methods: Electronic bibliographic databases including EMBASE, PubMed, Scopus, The Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), VIP Database, Wanfang Database and Chinese Biomedical Literature Database will be searched for relevant randomized controlled trials (RCTs) of non-pharmacological interventions for PPD. Heterogeneity and inconsistencies will be analyzed by I 2 statistic and Z test, respectively. We will assess the quality of evidence by the Grading of Recommendations Assessment, Development and Evaluation (GRADE) and evaluate the risk of bias according to Cochrane risk of bias tool. R software 3.6.1 (R Foundation for Statistical Computing, Vienna, Austria) will be used to conduct a network meta-analysis. Results: Formal ethical approval is not required, because the present study is a meta-analysis based on existed studies. The findings of this research will be reported in a recognized journal. Conclusion: The review results will ascertain the hierarchy of effectiveness of different non-pharmacological approaches for PPD, and systematically provide suggests for physicians and patients. Trial registration number: PROSPERO CRD42020166801